Pengaruh Variabel Peningkatan Produktivitas , Penguasaan Teknologi Baru dan Pelatihan Terhadap Pengendalian Mutu Terpadu Karyawan Pada Industri Tekstil dan Garmen di Surakarta - Ahmad Darmawi; Darsono Darsono (Politeknik APP Jakarta, 2018)
Integrated Quality Control requires the participation of all divisions within the company, such as marketing, design, manufacturing. Laboratory examination. As an integrated process that focuses on customers and beneficiaries, it simultaneously aims to protect and enhance the satisfaction of all stakeholders. Employee development does cost a lot, but it is a long-term investment for the company in personnel. Because skilled and skilled employees will be able to work more efficiently, effectively, wastage of raw materials, and less machine wear, better results will increase the company's competitiveness. The purpose of this research is (a) to know the level of Employee Productivity (TPK), (b) Employee Training (PK) and (c) Latest Technology Development (PTT) whether the positive effect on Integrated Employee Quality Control (PMTK). This research use Survey research method by using quantitative approach. The results obtained the employee Productivity Level positive effect on Integrated Quality Control Employees with 0,072 standardized coefficients. Employee Training has a positive effect on Integrated Employee Quality Control with a standardized coefficient of 0.164. Latest Technology Development positively influences to Integrated Quality Control Employee with a coefficient of standardized 0,114.